2011
DOI: 10.1590/s0100-736x2011001300003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic evaluation of dairy cows submitted to three different strategies to decrease the effects of negative energy balance in early postpartum

Abstract: In early lactation dairy cattle suffer metabolic alterations caused by negative energy balance, which predisposes to fatty liver and ketosis. The aim of this study was to evaluate the metabolic condition of high yielding dairy cows subjected to three treatments for preventing severe lipomobilization and ketosis in early lactation. Fifty four multiparous Holstein cows yielding >30 L/day were divided into four groups: control (CN= no treatment), glucose precursor (PG= propylene-glycol), hepatic protector (Mp= Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
3
16
1
3
Order By: Relevance
“…Triglyceridemia indicates the capability of liver for synthesis apolipoprotein B-100, VLDL for elimination of triglycerides in the blood stream during the whole peripartal period, but diminished concentration was significant on day 60 after calving, when NEFA concentrations were very low. These results agree with some previously published results from other investigators (8,10).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Triglyceridemia indicates the capability of liver for synthesis apolipoprotein B-100, VLDL for elimination of triglycerides in the blood stream during the whole peripartal period, but diminished concentration was significant on day 60 after calving, when NEFA concentrations were very low. These results agree with some previously published results from other investigators (8,10).…”
Section: Discussionsupporting
confidence: 94%
“…During the calving the glucose level rapidly increases, which is explained as a result of stress and hormonal status changes (5,6). After calving, during the early lactation, the glucose level is significantly lower compared with the period before calving (7,8), and this could be considered as introduction to NEB where synthesis of milk compounds in the mammary gland exceeds the gluconeogenesis capacities of liver, and leads to development of metabolic (production) diseases (8,9). Increased utilization of glucose by the mammary gland vs. decreased glucoplastic compounds input and decreased gluconeogenesis cause development of hypoglycemia, which very often could be associated with a disorder of the lipid metabolism (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of subclinical ketosis in western Santa Catarina was lesser (9%) than the values reported by other studies in the southern region of Brazil, as Gonçalves (2015) who mentioned an prevalence of 35% of this disorder or Garcia et al (2011) who found 24% in cows from the state of Rio Grande do Sul. Cucunubo et al (2013) found 14.8% of subclinical ketosis in dairy cows from southern Chile and Garro et al (2014) in Argentina found similar values of subclinical ketosis to our study (10.3%).…”
Section: Discussioncontrasting
confidence: 53%
“…The negative energetic balance of lactating cows that occurs during the few weeks postpartum shifts the hormonal profile of the animal [22]. These alterations may lead to metabolic disturbance as ketosis, lipid infiltration [5] and hypocalcaemia [16]. The serial levels of glucose, β-hydroxybutyrate (BHBA) and cholesterol are parameters that reveals liver condition and it is very important for the metabolism of milking cows [22].…”
Section: Introductionmentioning
confidence: 99%